2022
DOI: 10.1158/1078-0432.ccr-22-2088
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of MCL-1 Protein Stability Induced by MCL-1 Antagonists in B-Cell Malignancies

Abstract: Purpose: Several MCL-1 inhibitors (MCL-1i), including AMG-176 and AZD5991, have shown promise in preclinical studies and are being tested for the treatment of hematological malignancies. A unique feature of these agents is induction and stability of Mcl-1 protein; however, the precise mechanism is unknown. We aim to study mechanism of MCL-1i-induced Mcl-1 protein stability. Experimental Design: Using several B-cell leukemia and lymphoma cell lines and primary CLL lymphocytes, we evaluated molecular events asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Mcl-1 degradation is frequently mediated by the proteasomal pathway, which may be induced by phosphorylation of the PEST domain or through binding by proapoptotic Bcl-2 proteins and BH3 mimetics. Finally, Mcl-1 is a well-described target of caspase activity and is degraded in course of induced apoptosis [ 45 ]. In our experiments, Mcl-1 downregulation appeared to be related to induced caspase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mcl-1 degradation is frequently mediated by the proteasomal pathway, which may be induced by phosphorylation of the PEST domain or through binding by proapoptotic Bcl-2 proteins and BH3 mimetics. Finally, Mcl-1 is a well-described target of caspase activity and is degraded in course of induced apoptosis [ 45 ]. In our experiments, Mcl-1 downregulation appeared to be related to induced caspase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of MCL1 or BCLXL was similarly toxic to venetoclax-resistant AML cell lines when given in combination with venetoclax [ 107 ]. Clinical research on MCL1 inhibitors is in the early stage, and potential cardiac interactions are currently being investigated [ 108 ].…”
Section: Bcl2 Inhibitorsmentioning
confidence: 99%
“…However, the mechanism of this protein accumulation is largely unknown. To address this knowledge gap, Tantawy et al explored underlying molecular mechanisms that contribute to MCL1i-induced MCL-1 protein accumulation and its implications [ 14 ].…”
mentioning
confidence: 99%
“…However, this effect was reversible following withdrawal of MCL-1i, indicating a direct effect of the drug on MCL-1 protein stability. Using protein-protein interaction studies, immunoprecipitation (IP) and co-IP experiments, Tantawy et al [ 14 ] showed that MCL-1i-induced defective ubiquitination of MCL-1 protein. This indicates that the upregulation of MCL-1 protein is not due to direct proteasomal inhibition, but rather due to interference with the ubiquitination and/or enhancing de-ubiquitination of MCL-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation